MODEL PEMILIHAN MODA OLEH PELAJAR UNTUK TUJUAN SEKOLAH - Anggraini, Renni; Mutiawati, Cut; Jauhari, M. Khair (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Due to improper public transport services in Banda Aceh City, most students tend to use motorcycle for daily activity, in particular to school. Those who use public transport are rarely found. As a result, it will contribute to traffic congestion. This study aimed to investigate mode choice model of students to school. The location takes place at Kecamatan Meuraxa, Banda Aceh City, limited to high school students that use motorcycle and public transport to school. Primary data was done by conducting home interview survey. The method used were binomial logit difference and ratio take into account  travel time, cost and waiting time as the independent variables.  The results showed 67% students used motorcycle to school, and those who have SIM C was about 59%. Both models showed, when the cost of both modes are equal, about 50-60% of students used motorcycle to school.